Development and Implementation of a Virtual High Performance Liquid Chromatography (HPLC) Laboratory to Enhance Learning Outcomes in Analytical Chemistry - Diva Angelica Amanda Batubara Batubara; Manihar Situmorang (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
In the implementation of High Performance Liquid Chromatography (HPLC) learning, in addition to understanding the material, students must conduct practical work to effectively understand the system and operation of HPLC instrumentation. However, due to the limitations of facilities and access to physical laboratories for HPLC instrumentation, an innovative learning resource, namely the Virtual HPLC Laboratory, has been developed. This study aims to evaluate the improvement in student learning outcomes and motivation through the use of Virtual High Performance Liquid Chromatography (HPLC) laboratory media in HPLC learning. This research was conducted in the Chemistry Department of Universitas Negeri Medan during the even semester of the 2025 academic year. This study employs a Research and Development (R&D) approach with a 4D (Four-D) development model. The research sample consists of class PSKM 23 B as the experimental group and class PSKM 23 A as the control group, which were selected through total/saturation sampling method. The implementation of the Virtual HPLC Laboratory developed in this study has several findings, namely: (1) The developed virtual laboratory is effective for use in learning (2) The developed Virtual HPLC Laboratory meets the modified criteria of the National Education Standards Agency (BSNP) (3) The Virtual HPLC Laboratory effectively improves the learning outcomes of analytical chemistry separation (4) Through a two-sample t-test, it has been proven that there is an effect of using the Virtual HPLC Laboratory media on students' learning outcomes in teaching analytical chemistry separation (5) Through an independent sample t-test, it has been proven that there is a difference in students' learning outcomes who are taught using the Virtual HPLC Laboratory compared to those taught using student guide learning resources. (6) through the completion of a student learning motivation questionnaire, it can be concluded that the use of the Virtual HPLC Laboratory affects and enhances students' learning motivation in HPLC training.